2017
DOI: 10.1111/1758-2229.12550
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and ecology of and biomineralization by magnetotactic bacteria

Abstract: Magnetotactic bacteria (MTB) biomineralize intracellular, membrane-bounded crystals of magnetite (Fe O ) and/or greigite (Fe S ) called magnetosomes. MTB play important roles in the geochemical cycling of iron, sulfur, nitrogen and carbon. Significantly, they also represent an intriguing model system not just for the study of microbial biomineralization but also for magnetoreception, prokaryotic organelle formation and microbial biogeography. Here we review current knowledge on the ecology of and biomineraliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(106 citation statements)
references
References 133 publications
(183 reference statements)
0
106
0
Order By: Relevance
“…Representatives of this group are present in a number of phyla including several classes of the Proteobacteria (Sakaguchi et al ., ; Lefèvre et al ., ; Morillo et al ., ; Taoka et al ., ; Abreu et al ., ), the Nitrospirae (Lefèvre et al ., ; Lin et al ., ) and the candidate phylum Omnitrophica (Kolinko et al ., , ). Culture‐independent methods and single‐cell genome analysis indicate that the diversity and phylogenetic distribution of magnetotactic organisms are underestimated (Kolinko et al ., ; Rinke et al ., ) and may extend to other phylogenetic groups including the phyla Latescibacteria and Planctomycetes (Lin and Pan, ; Lin et al ., ; Lin et al ., ) or maybe even other domains of life (Torres de Araujo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Representatives of this group are present in a number of phyla including several classes of the Proteobacteria (Sakaguchi et al ., ; Lefèvre et al ., ; Morillo et al ., ; Taoka et al ., ; Abreu et al ., ), the Nitrospirae (Lefèvre et al ., ; Lin et al ., ) and the candidate phylum Omnitrophica (Kolinko et al ., , ). Culture‐independent methods and single‐cell genome analysis indicate that the diversity and phylogenetic distribution of magnetotactic organisms are underestimated (Kolinko et al ., ; Rinke et al ., ) and may extend to other phylogenetic groups including the phyla Latescibacteria and Planctomycetes (Lin and Pan, ; Lin et al ., ; Lin et al ., ) or maybe even other domains of life (Torres de Araujo et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Previous biodiversity studies revealed the intriguing polyphyletism of magnetic biomineralization within the bacteria domain (Lin et al, 2018). Most of the MTB described so far belong to three classes of Proteobacteria, and some are affiliated to the Nitrospirae and Omnitrophica phyla Lin et al, 2017a). Recent metagenomic data suggested that some bacteria within the Latescibacteria and Planctomycetes phyla could also biomineralize (Lin et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…QH-2 whose region harbouring the magnetosome genes contains few or no mobile elements and present a high stability within the genome (Lefèvre et al, 2011;Ji et al, 2014). Because different strains may support different evolutionary scenarios, it is difficult to arbitrate between vertical and horizontal inheritance, which feeds a permanent debate (Lefèvre et al, 2013a;Lin et al, 2017a).…”
Section: Introductionmentioning
confidence: 99%
“…MTB signature genes in metagenomic sequences obtained from Sakinaw Lake (Canada), a lake where the pH varies from 5.7 to 6.5 and the temperature ranges from 8 to 19 C (Perry, 1990), strongly indicate the possibility of a novel greigite-producing MTB belonging to the candidate phylum 'Latescibacteria' (formerly WS3) (Lin and Pan, 2015) although an MTB of this type was not physically observed from the lake. Recently, a partial greigite-type magnetosome gene cluster has been identified in a draft genome from a bacterium affiliated to Planctomycetes phylum obtained from the sediment of the White Oak River, North Carolina (Lin et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…These strains grow optimally at pH 9.0-9.5, but not at pH 8.0 (Lefèvre et al, 2011). Different morphotypes of MTB have also been found in saline-alkaline lakes in Inner Mongolia, China (Lin et al, 2017). An uncultured moderately thermophilic MTB from the Nitrospirae phylum was discovered in hot spring sediments collected from Great Boiling Springs, Nevada (Lefèvre et al, 2010).…”
Section: Introductionmentioning
confidence: 99%